Pidana Pemidanaan Tindakan Bagi Anak Sebagai Pencurian Dengan Kekerasan (Studi Kasus Putusan Nomor 20/Pid.Sus-Anak/2020/PN Jkt.Pst) - Dadang Setiawan (Peneliti.net, 2023)
The Panel of Judges of Court Number 20/Pid.Sus-Anak/2020/PN Jkt.Pst on the perpetrators of the crime of theft with violence committed by children in the Decision. However, the Panel of Judges based on legal facts as a form of social justice in the community, the Judge still stated that the child Muhammad Fadillah Alias Ambon had been proven legally and convincingly guilty of committing the crime of